Avaliação da resistência de Rhipicephalus Microplus a Acaricidas comercializados no Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Considering the lack of information on acaricide drug resistance in the Lower Amazon region, we aimed to determine the efficiency of three acaricide products Amitraz, Cypermethrin and Deltamethrin in controlling the tick Rhipicephalus microplus. The adult immersion test was used on female ticks sampled on a farm in the Lower Amazon. For the test, homogeneous batches of 10 engorged females were placed in Petri dishes, using four plates for each test acaricide, which were immersed in the products and three plates as a negative control, immersed in distilled water. The acaricides were diluted as recommended by the manufacturers and the ticks were submerged for five minutes. Mortality of engorged females, egg mass and percentage of larval hatching were evaluated. For Amitraz 2.5%, 7.1 and 53.7% respectively, Cypermethrin 7.5%, 42.7 and 88.7% and Deltamethrin 0%, 39.6, 80.0%. As recommended by the FAO, for the acaricide to be considered effective, it must have a control ≥ 95%, among the tested acaricides, Amitraz showed efficacy of 90.5%, Cypermethrin 10.4% and Deltamethrin 26.6%. Ticks from the lower Amazon showed marked resistance to Cypermethrin and Deltamethrin and mild resistance to Amitraz.
Keywords: Controle; Acaricidas; Eficiência; Teleóginas; CNPQ:: CIÊNCIAS AGRÁRIAS